Quality of life in the context of sustainable development - Zadrozniak, Monika (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The article shows interpretation relationship and interdependence of the two conceptual categories: quality of life and sustainable development. This article puts the claim of social, economic and environmental dimensions of sustainable development expressed in the quality of life of the inhabitants of the region (place), interpreted as the overarching goal of development.